Gaya Kepemimpinan Pada Perusahaan Multinasional: Systematic Literature Review - Ratna Mitasari; Madziatul Churiyah; Arief Noviarakhman Zagladi (CV. ITTC INDONESIA, 2024)
This research aims to find out what leadership styles are applied by multinational companies in the era of globalization. This research method is a systematic literature review, the journal data source was taken from the ScienceDirect and Emerald Insight websites of 12 journals. The research results show that the application of leadership styles in multinational companies, several previous journal studies provide the argument that many companies use or apply a transformational leadership style that always strives to improve the development of the organization globally. Apart from that, the transformational leadership style can influence the knowledge and innovation that multinational companies can develop